Aquaporin-8 transports hydrogen peroxide to regulate granulosa cell autophagy - Huang, Binbin; Jin, Lingling; Zhang, Luodan; Cui, Xiaolin; Zhang, Zhen; Lu, Yongqi; Yu, Lujia; Ma, Tonghui; Zhang, He (Frontiers in Cell and Developmental Biology, 2022)
Aquaporin-8 (AQP8), a member of the aquaporin family, is strongly expressed in follicular granulosa cells, which could affect the hormone secretion level in females. AQP8, as a membrane protein, could mediate H2O2 into cells, thereby triggering various biological events. The deficiency of Aqp8 increases female fertility, resulting from the decrease in follicular atresia. The low cell death rate is related to the apoptosis of granulosa cells. However, the mechanism by which AQP8 regulates the autophagy of granulosa cells remains unclear. Thus, this study aimed to explore the effect of AQP8 on autophagy in follicular atresia. We found that the expression of the autophagy marker light-chain protein 3 was significantly downregulated in the granulosa cells of Aqp8-knockout (Aqp8−/−) mice, compared with wild-type (Aqp8+/+) mice. Immunofluorescence staining and transmission electron microscopic examination indicated that the number of autophagosomes in the granulosa cells of Aqp8−/− mice decreased. Using a follicular granulosa cell autophagy model, namely a follicular atresia model, we verified that the concentration of H2O2 significantly increased during the autophagy of granulosa cells, consistent with the Aqp8 mRNA level. Intracellular H2O2 accumulation was modulated by endogenous AQP8 expression level, indicating that AQP8-mediated H2O2 was involved in the autophagy of granulosa cells. AQP8 deficiency impaired the elevation of H2O2 concentration through phosphorylated tyrosine activation. In addition, we carried out the analysis of transcriptome sequencing datasets in the ovary and found there were obvious differences in principal components, differentially expressed genes (DEGs) and KEGG pathways, which might be involved in AQP8-regulated follicular atresia. Taken together, these findings indicated that AQP8-mediated H2O2 transport could mediate the autophagy of granulosa cells. AQP8 might be a potential target for diseases related to ovarian insufficiency.